Vesnice či již město? Neolit a počátky urbanizace Evropy - Josef Dufek (AntropoWebzin, 2014)
The purpose of this paper is to acquaint the reader with the majortrends of proto-urban settlements in the Near East since the beginnin gof Pre-pottery Neolithic (PPN) to the Early Chalcolithic (10/9000 BC– 6000 BC) and the Early Neolithic to the Early Eneolithic Southeast Europe (6 500 – 4500 BC).